2005
DOI: 10.5751/es-01285-100108
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Informal Protected Areas in Maintaining Biodiversity in the Western Ghats of India

Abstract: Although it is widely believed that an important function of protected areas is to conserve species that are unable to survive elsewhere, there are very few empirical studies in which a comparison is made between biodiversity of protected areas and that of the cultivated landscape surrounding them. We examined the diversity of trees, birds, and macrofungi at 58 sites in three land-use types in a tree-covered landscape in Kodagu district in the Western Ghats of India. Ten forest reserve sites in the formal prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(95 citation statements)
references
References 45 publications
4
89
0
2
Order By: Relevance
“…In Tanzania, the size of eight surveyed sacred groves varies from 0.1-0.3 ha (Mgumia and Oba 2003). In southern India, the average size of sacred groves is 13.2 ha (n = 25, range 0.2-48.1 ha) (Bhagwat et al 2005b), and the average size of sacred groves throughout India is estimated at 9.6 ha (n = 4415, total area = 42,278 ha) (Malhotra 2001). These small sacred groves can be effective in protecting endangered species (Jamir andPandey 2003, Ramanujam andCyril 2003), but are unable to conserve the entire ecosystem.…”
Section: Tibetan Sacred Sites Serve As a Landscape-level Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tanzania, the size of eight surveyed sacred groves varies from 0.1-0.3 ha (Mgumia and Oba 2003). In southern India, the average size of sacred groves is 13.2 ha (n = 25, range 0.2-48.1 ha) (Bhagwat et al 2005b), and the average size of sacred groves throughout India is estimated at 9.6 ha (n = 4415, total area = 42,278 ha) (Malhotra 2001). These small sacred groves can be effective in protecting endangered species (Jamir andPandey 2003, Ramanujam andCyril 2003), but are unable to conserve the entire ecosystem.…”
Section: Tibetan Sacred Sites Serve As a Landscape-level Conservationmentioning
confidence: 99%
“…Sacred sites have been under the protection of local people for their spiritual value for generations and might be the oldest forms of protected areas in human history (Dudley et al 2009). It has been shown that the traditional practice of sacred site worship may make significant contributions to protecting endangered species and conserving biodiversity (Decher 1997, Mgumia and Oba 2003, Bhagwat et al 2005a, 2005b, Bossart et al 2006, and few studies have documented the social mechanisms behind those traditional practices (Malhotra 2001, Tengö et al 2007. Recognizing the value of sacred sites in contemporary conservation systems is advocated by numerous scholars and international nongovernmental organizations (NGOs) and has received increasing attention over the last two decades (Daniels et al 1993, Xu et al 2005, Bhagwat and Rutte 2006, Dudley et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…These are the new areas of Indigenous education which must be explored and operationalized in the context of Indigenous education toward the development and revitalization of Indigenous communities as they face the challenges of surviving the ecological, social and political challenges of a twenty first century world. (Bhagwat et al 2005). Combining the two kinds of knowledge is especially important in situations of insufficient information.…”
Section: Sustaining Indigenous Community In the Context Of Climate Chmentioning
confidence: 99%
“…Some biodiversity is under state ownership, some is under the control of communities, and some is privately owned. Many of the lands that support biodiversity are under multiple and competing claims, including nominally government-owned forests under community control (5); protected areas designed for biodiversity conservation but that allow for human use, as with the World Conservation Union's protected-area categories V and VI (www.unep-wcmc.org/protected areas/ categories/index.html); and locally maintained traditional protected areas, such as the sacred groves of Kerala, India, which can be as effective as nearby government protected areas (6).…”
mentioning
confidence: 99%